PENGARUH PEMBERIAN STIMULASI PERKEMBANGAN PADA ASPEK SOSIALISASI TERHADAP STATUS PERKEMBANGAN PERSONAL SOSIAL ANAK PRASEKOLAH DI TK SAPTA KRIDA KABUPATEN GORONTALO - Andi Akifa Sudirman; Dewi Modjo (-, 2021)
Stimulastion is an important necessity for the groth and evolution of children. The child who has much stimulation would be fast growth from the child who get lack stimulation. This research was conducted at Sapta Krida Kindergarten Gorontalo District. This research aims to identified the influence of giving developmental stimulation on socialization aspects of the social personal development status in preschool children. Design used quasi eksperimental one group pre test - post test. The samples are 23 children, 4 - 5 years old (48 - 60 month) with simple random sampling technique. The instrument used questionnaire of social personal development. Statistical test used T-test dependent on social personal development status of the child before and after intervention that obtained significancy 0,000 (p-value < 0,05) therefore could be concluded there are meaningful influence between giving stimulation on increasing status of child’s social personal development.